2016
DOI: 10.17085/apm.2016.11.1.91
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of warming methods for core temperature preservation during total knee arthroplasty using a pneumatic tourniquet

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution Non-Commercial License (http://creativecommons.org/licenses/by-nc/4.0) which permits unrestricted non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited. Background:It is important to ensure that patients are normothermic during surgery. In total knee arthroplasty, the pneumatic tourniquet affects body temperature. We compared the ability of two warming devices … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…[ 10] have shown that the use of fluid warmer or forced-air warmer devices effectively preserves the core body temperature after tourniquet deflation at the total knee arthroplasty.…”
Section: Methodsmentioning
confidence: 99%
“…[ 10] have shown that the use of fluid warmer or forced-air warmer devices effectively preserves the core body temperature after tourniquet deflation at the total knee arthroplasty.…”
Section: Methodsmentioning
confidence: 99%